PENALARAN INDUKTIF SISWA SMA DALAM MENYELESAIKAN MASALAH TRANSFORMASI GEOMETRI - Serli Evidiasari; Subanji Subanji; Santi Irawati (Jurnal Kajian Pembelajaran Matematika, 2019)
This study describes the inductive reasoning  of high school students in solving geometry transformation problems.The steps of inductive reasoning in mathematics namely: (1) discussing pattern that occur, (2) making guesses about general patterns that might apply, (3) making generalizations, (4) proving generalizations deductively. The assesment used in this study is descriptive qualitative. The data source is the result of a geometry transformation test involving 35 students grouped by ability are high, intermediate and low. Then select 3 students who represent each group. The results of this study are high ability students can perform all streps of inductive reasoning and the answer given are appropriate, capable students are able to take all the steps but  still make some fault in generalizaton step, low ability student can analyze data only and  can not interpret mathematical symbols.